Comparison of the symptoms reported by post-operative patients with cancer and nurses' perception of patient symptoms. - Guner, C K; Akin, S; Durna, Z (My University, 2015)
The purpose of this study was to compare the symptoms reported by patients with cancer after palliative surgery and mechanical ventilation in an intensive care unit (ICU) with their primary nurses' perception of the symptoms. The study adopted a descriptive and correlational study design. The sample comprised 60 Turkish patients with cancer who had been mechanically ventilated for 1-12 h at the ICU following palliative surgery. In addition to the patients' reports, the nurses (= 8) independently rated their own perceptions of the patients' symptoms. Data were collected using the Edmonton Symptom Assessment Scale (ESAS). The mean age of the sample was 62.28 years (SD = 15.02; range: 27-86). The mean score of the patients on the ESAS was 55.17 (SD = 26.16) and that of the nurses was 55.48 (SD = 27.13). The study found no statistically significant differences between scores of patients' reports and nurses' assessments of symptoms, except for the category of pain. Patients reported more pain than the nurses' perceived (Z = -2.311, P = 0.021). Systematic and frequent symptom assessments of patients in ICUs after palliative surgical operations should be an integral part of nursing care.
Keywords: Adult; Aged, 80 and over; Male; Pain, Postoperative; Turkey; Attitude of Health Personnel; Palliative Care; Nurses; Middle Aged; Intensive Care Units; Neoplasms; Humans; Female; Perception; Postoperative Period; Self Report; Symptom Assessment; Aged; Pain Measurement; 3. Good health